MAKNA GUMBREGAN TERHADAP KEHIDUPAN SOSIAL KEAGAMAAN MASYARAKAT PETANI DI SAPTOSARI, GUNUNGKIDUL - Nur Laili Maharani (Religi: Jurnal Studi Agama-agama, 2019)
Ritual is religion in action. gumbregan is one of the rituals carried out every year by the community of Saptosari Gunungkidul. This ritual is only carried out by Gunungkidul farmers who have cattle. Cows as pets that are considered meritorious for the people of Saptosari who mostly work as farmers because they help in cultivating agricultural land. The gumbregan ritual is held every seven months at the time of Wuku Gumbreg (Javanese calendar). The purpose of the gumbregan ritual is related to the myth of the farmer, they have hope that the atmosphere is peaceful and avoid negative things, such as disturbing the peace of the soul. The author uses the theory of Victor Turner's liminality which analyzes the state of society when performing religious rituals and for studying aspects of the ritual. The author explains this gumbregan ritual using a field research data source. Which is supported by using the method of observation, interviews, documentation, and processed using descriptive analytical methods. This ritual is interpreted as a warning to the prophet Sulaiman who has ruled all animals in the universe, a form of gratitude to God, and as a step to unite the community in order to create safe and peaceful living conditions so as to foster a sense of togetherness in social matters.Keywords: Gumbregan ritual, religious social life, farming community.